The demographic and socioeconomic correlates of behavior and HIV infection status across sub-Saharan Africa - Chirag J. Patel; Kajal T. Claypool; Eric Chow; Ming-Kei Chung; Don Mai; Jessie Chen; Eran Bendavid (Communications Medicine, 2022)
Patel et al. perform a comprehensive analysis of factors associated with HIV positivity across 29 sub-Saharan African countries from 2003 to 2017. They identify over 300 factors associated with HIV positivity in each sex, some of them under-recognized but consistent across countries and sex.